Talent Management Strategies and Their Impact on the Well-Being of Healthcare Workers: A Literature Review - Rukman, Rukman; Sakka, Moh.Nasir; Fadil, Medriono; Alinda, Yayu; Kadri, Abdul (Devotion : Journal of Research and Community Service, 2026)
Healthcare workers are a key resource in the healthcare system, playing a crucial role in maintaining service quality and patient safety. The various work challenges faced by healthcare workers require a human resource management strategy that focuses not only on organizational performance but also on their well-being. One relevant strategic approach is talent management. This study aims to examine talent management strategies and their impact on healthcare worker well-being through a Systematic Literature Review (SLR) using the PRISMA approach. A literature search was conducted in Google Scholar, PubMed, and ScienceDirect databases for articles published between 2021 and 2026. A total of 15 journals that met the inclusion criteria were analyzed descriptively. The study results indicate that talent management strategies, including competency development, career planning and development, reward and compensation systems, effective leadership, and the use of digital technology, have a positive impact on healthcare worker well-being, reflected in increased job satisfaction, motivation, and professional well-being. However, the implementation of talent management still faces several challenges, such as limited resources and high workloads. Therefore, ongoing organizational commitment and policies are needed to optimize the implementation of talent management to support healthcare worker well-being and the sustainability of the healthcare system